Monochord to moog : a study of the development of stringed keyboard instruments with special reference to popularity trends - Shuttleworth, Betty (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1972)
The object of the present work has been to trace the evolution of stringed keyboard instruments from the monochord to the present day piano forte. So many inventions have occurred that a chronology of these would be both tedious and of little added value to the existing literature. In the present work the emphasis has been on those innovations which achieved some measure of popularity and can be regarded as essential steps in arriving at the products and methods of modern piano manufacturers. In order to bring this work up to date, visits have been paid to John Broadwood & Sons and the British Piano Museum in London; to the Essex Institute and Pingree House in Salem, Massachusetts; the Smithsonian Institute (Division of Musical Instruments) in Washington; the various Yamaha Factories in Hamamatsu, Japan; and the Piano Manufacturing Company in Wellington, South Africa. Special attention has also been paid to the development and popularity trends of mechanical, pneumatic and electric pianos. In the last Chapter of this study, the information gained is applied to the identification and dating of stringed keyboard instruments found in South Africa or referred to in newspapers or Africana.
Keywords: Keyboard instruments -- History